PENGUKURAN RESISTIVITAS PADA DAERAH DUGAAN SUMBER PENYEBAB ANOMALI GEOMAGNETIK DI PULAU LOMBOK NTB - Kanata, Bulkis; Zubaidah, Teti; Utama, Widya; Warnana, Dwa Desa; Ramadani, Cipta (Jurnal Teknologi Elektro; Vol 8 No 1 (2009): Jurnal Teknologi Elektro, 2012)
possibilities of the source of geomagnetic anomaly in Lombok Island, i.e. a specific local structure composed by a quite large magnetic body or a local fault in this region that could be associated with a source of seismic hazard (especially earthquakes). An interesting profile could be estimated lie around the minimum geomagnetic anomaly (8 0 45’36”S, 116 0 1’48”E) to the maximum one (8 0 43’48”S, 116 0 5’24” E). Understanding the corresponding structure on that profile is very important - related to the possibility of the source of geomagnetic anomaly in Lombok Island - in order to get further information about potentially local fault in this region as a source of earthquakes hazard. Geoelectric method with vertical electrical sounding (VES) configuration have been applied in this profile, on three VES points (i.e. one point between the minimum and the maximum geomagnetic anomaly (X 1 : 8 0 46’42.9”S, 116 0 04’07.7”E), and two other points outside (X 2 : 8 0 46’03.3”S, 115 0 58’39.9”E; which is on negative anomaly area) and (X 3 : 8 0 42’11.6”S, 116 0 08’27.2”E; which is on positive anomaly area). The potency of X 1 as a critical zone has been shown, with the existence of resistivity contrast in this area, which its resistivity value between X 2 (very high resistivity; r >25,000 Wm) and X 3 (very low resistivity; ; r >1 W m). This results lead to the potentially local fault in this region as a source of earthquakes hazard.